Praxis der Individualisierung Wie multiprofessionelle Klassenteams Fördersituationen für Kinder im Schulalltag etablieren - Widmer-Wolf, Patrik (Verlag Barbara Budrich, 2014)
How do individualised support arrangements for children with special educational needs come about in integrative/inclusive teaching? The author describes how different understanding of cooperation between occupational groups goes hand in hand with different concepts of individualisation and is anchored in different institutional experiences: a differentiated analysis for the reconstruction of action orientations in the reform process at the school entry level.